2021
DOI: 10.1021/acsami.1c01400
|View full text |Cite
|
Sign up to set email alerts
|

Condensation Behavior of Hierarchical Nano/Microstructured Surfaces Inspired by Euphorbia myrsinites

Abstract: In nature, many extant species exhibit functionalized surface structures during evolution. In particular, wettability affects the functionalization of the surface, and nano/microstructures have been found to enable functions, such as droplet jumping, thereby making self-cleaning, antifog, antibacterial, and antireflection surfaces. Important efforts are underway to understand the surface structure of plant leaves and establish rational design tools for the development of new engineering materials. In this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…2A). Inspired by E. myrsinites , Baba et al 27 fabricated biomimetic microcolumn arrays with superhydrophobicity and low adhesion on silicon wafers. Optical observation by microscope revealed that when the height of the microcolumn reached 6.5 μm, the mass transfer coefficient increased rapidly with the steam diffusion rate, and the greater disturbance of the local mass transfer boundary layer provided the corresponding abundant steam for the formation and growth of the bottom droplets; thus tiny droplets are formed at the bottom of the coalesced droplets, which grow and merge with the secondary droplets to motivate the continuous jump of surface droplets (Fig.…”
Section: Structures For Antifoggingmentioning
confidence: 99%
“…2A). Inspired by E. myrsinites , Baba et al 27 fabricated biomimetic microcolumn arrays with superhydrophobicity and low adhesion on silicon wafers. Optical observation by microscope revealed that when the height of the microcolumn reached 6.5 μm, the mass transfer coefficient increased rapidly with the steam diffusion rate, and the greater disturbance of the local mass transfer boundary layer provided the corresponding abundant steam for the formation and growth of the bottom droplets; thus tiny droplets are formed at the bottom of the coalesced droplets, which grow and merge with the secondary droplets to motivate the continuous jump of surface droplets (Fig.…”
Section: Structures For Antifoggingmentioning
confidence: 99%
“…Meanwhile, condensate micro droplets on liquid-repellent surfaces with nanostructures could be selfpropelled since the coalescence-released excess surface energy was much larger than the interface adhesion-induced energy dissipation. 51,183,[443][444][445][446][447][448] For example, as shown in Fig. 33, Wang et al demonstrated that condensate micro droplets on a superhydrophobic surface with closely packed aligned ZnO nanoneedles could be self-removed by mutual coalescence-induced jumping, and the surface thereby maintained long-term water repellence in extreme vapor conditions.…”
Section: Nano Structuresmentioning
confidence: 99%
“…74a, also see Section 4.2.2) are desired for heat transfer enhancement. [33][34][35]51,443,444,446,448,687 For example, Miljkovic et al prepared nanostructured CuO films on Cu tube surface by chemical oxidation in a hot alkaline solution composed of NaClO 2 , NaOH, Na 3 PO 4 Á12H 2 O, and deionized water (3.75 : 5 : 10 : 100 wt%), which were then functionalized by using CVD of a fluorinated silane (trichloro(1H,1H,2H,2Hperfluorooctyl)silane). 687 As shown in Fig.…”
Section: Enhanced Heat Transfermentioning
confidence: 99%
“…Steam condensation/droplet freezing on solid surfaces can cause serious economic and safety problems. Thus, highly efficient antifogging/anti-icing approaches are vital in many engineering applications, involving aerospace, wind/photovoltaic power generation, refrigeration, transportation, and power communication. Typical solutions to these problems are achieved by using active deicing systems such as electrothermal heating devices. However, the abovementioned methods have their limitations, such as high energy consumption, low efficiency, and nonenvironmental protection.…”
Section: Introductionmentioning
confidence: 99%